Village government innovation towards smart villages for smart services study in Bintangsari village, Cipanas sub-districk, Lebak districk - Eli Apud Saepudin; Rizki Amilia; Ita Rosita Wahyiah (Institute Of computer Science (IOCS), 2023)
The village is the smallest government after the sub-district where the village is part of the government that cannot be separated by the community as the main actor in receiving public services. Villages are the joints of the people's economy that support the regional economy and the national economy, one of the village products that can support the regional economy and the national economy at the same time is the staple food products of the smart village for smart services program which aims to increase the productivity of rural communities accompanied by an increase in annual income, supporting national food self-sufficiency, supporting the fulfillment of TKDN, supporting regional and national economies through village administration and management systems, public services for village communities transparency and village information, village financial governance (Bumdes Bersama, Village Market) E-Commerce which is a breakthrough from smart villages for smart services to become a Pilot Village in Indonesia. To realize smart villages and the best services, there needs to be synergy between village officials and local communities so that smart villages can be realized well when collaborating with each other to create excellent services.